Wspólne wartości społeczeństwa holenderskiego - Lipnicka, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
Due to the growing multiculturalism and socio-ideological changes in the Netherlands, there hasemerged a need to define common values for the whole society. In the article, these values are analysed from two perspectives: historical changes (since the time the Republic was founded, through the pillarisation, and the transformation of the 1960s to the present day) and the current status quo, analysed with empirical research data. The analyses conducted in the article allow the conclusion that the Dutch society shares values related to civic and democratic culture, including freedom, equality and solidarity.